PENGARUH EDUKASI MENGGUNAKAN MEDIA BUKU CERITA BERGAMBAR TERHADAP PENGETAHUAN DAN KETERAMPILAN PENCEGAHAN KARIES GIGI PADA ANAK DI SD KEDUNGKANDANG 2 - Faiz Assan Wiratama Tama; Tavip Dwi Wahyuni (JPK : Jurnal Penelitian Kesehatan, 2026)
Dental caries is a health problem with high prevalence among elementary school children in Indonesia (84.8%). At SD Kedungkandang 2, the prevalence of caries reached 74.6%, higher than the average in the Kedungkandang Health Center working area (62.9%). Picture storybook media is suitable for the cognitive characteristics of third-grade elementary students who can read fluently and are interested in visuals. To analyze the effect of education using picture storybook media on knowledge and skills in dental caries prevention. A pre-experimental design with one-group pre-post test was conducted on 44 third-grade students selected by simple random sampling. Data were collected using knowledge questionnaires and skill observation sheets before and after education. Data analysis used the Wilcoxon test (?=0.05). Knowledge increased significantly from a mean of 65 to 85.8 (p<0.001), and skills improved from a mean of 64.5 to 83.0 (p<0.001). After education, 79.5% of students had good knowledge and 88.6% had good skills. Education using picture storybook media has a significant effect on improving knowledge and skills in dental caries prevention among students at SD Kedungkandang 2.